The whole library handbook : teen services - Booth, Heather, 1978-; Jensen, Karen, 1972- (ALA Editions, an imprint of the American Library Association, 2014)
ALA's popular and respected Whole Library Handbook series continues with a volume specifically geared towards those who serve young adults, gathering stellar articles and commentary from some of the country's most innovative and successful teen services librarians. Sections focusing on practice, theory, and the philosophical underpinnings of the profession are supported by current research and historical perspectives.